5. PRONUCLEAR (1976 – 1986) and the training of human resources for the area of nuclear energy in Brazil - Schmiedecke, Winston Gomes; Porto, Paulo Alves (Circumscribere International Journal for the History of Science, 2008)
This paper analyzes some aspects of the process of creating specialized human resources in nuclear technology during the extent of the agreement between Brazil and West Germany, by focusing on the PRONUCLEAR (Nuclear Sector Human Resources Program). Although not many, some important positive results can be identified from the analysis of reports describing the work and track record of PRONUCLEAR: the creation of specialized training programs in nuclear technology; the improvement and redirection of the curricula of courses related to its objectives – thus fostering the creation of an expressive number of technicians, masters and doctors in nuclear energy and related fields.